Cases of severe Clostridium difficile colitis proceeding with symptoms of peritonitis - E. I. Belinskaya (Acta Biomedica Scientifica, 2015)
Recently there was an increase of Clostridium difficile infection cases with the development of severe pseudomembranous colitis with high mortality and high percentage of backsets. Major reason for this growing problem is the emergence of newer, more virulent and more antibiotic-resistant strains including PCR ribotype 027. The major risk factors for pseudomembranous colitis are hospitalizing, antibiotics exposure, chemotherapy, use of proton-pumps inhibitors, older age, concomitant diseases. The appearance of diarrhea, acute abdominal pain, leukocytosis, hypoproteinemia after antibiotic therapy should be considered as a basis for targeted diagnostics of pseudomembranous colitis with the use of laboratory tests. Fulminant pseudomembranous colitis occurs in 5 % of patient with Clostridium difficile infection. This patients often have severe abdominal pain and can have signs of peritonitis and a markedly increased white blood cells. Colectomy should be considered in patients with fulminant colitis. The mortality rate in fulminant pseudomembranous colitis is up to 70 %. The basis for the prevention of pseudomembranous colitis is a rational prescription of antibacterial agents.